Intelligent mobile augmented reality application - Koh, Luo Hao (Nanyang Technological University, 2022)
In 1838, the invention of Charles Wheatstone’s stereoscope led to the birth of Augmented Reality (AR) and Virtual Reality (VR). Since then, AR and VR technology has evolved rapidly and is quickly becoming recognized as a helpful tool for manufacturers and not just a toy for consumers. Virtual reality (VR) immerses the user entirely in a digital world; once you put on the googles, the real world disappears. While VR can be helpful for training and creating prototypes, it can be dangerous to use in an active environment like a manufacturing floor. However, augmented reality (AR) superimposes digital information onto your view of the real world. Because AR remains rooted in what’s happening around you, AR can be used for many day-to-day tasks in industrial and manufacturing settings. Engineers can create digital overlays to see what features will look like next to real-world objects. This provides visibility into the final product throughout the design phase so that Trainers can record training modules that help employees complete their tasks using an AR headset. This is beneficial for complex tasks that are difficult to explain and comprehend using standard formats like text or video. Augmented reality is not limited to the abovementioned industries and can be extended to retail. AR can help reduce customer journey by enabling them to try out products virtually before buying them and see exactly how a piece of new furniture will look or how a piece of clothing will fit them in their home or office environment. This project aims to implement an AR-based glass try-on application to enhance the glass shopping experience. The application utilizes AR face tracking to identify facial landmarks and project virtual glasses onto the customer’s face. Face tracking is also used to scan a customer’s face shape and take down their measurements to ensure they get a set of glasses customized to their exact specifications. Various functionalities like a recommendation feature, screenshot feature and check-out functionality are also included to provide users with an enhanced and complete shopping experience.